RELEVANSI FAKTOR PENENTU PERLUASAN MISI GEREJA MULA-MULA BAGI MISI SEDUNIA - Sostenis Nggebu (Sekolah Tinggi Teologi Excelsius, 2022)
ABSTRACT: The problem of this article examines the challenging and decisive factors for the expansion of the mission of the Early Church in Asia Minor, from Jerusalem to Rome. These determining factors allow the expansion of the Church's mission to be used as a benchmark for the church throughout the centuries in mission. The study of this article uses a descriptive method. The results show that the early Christians carried out the Great Commission for the expansion of the church's mission because it was supported by the obedience of their leaders and members of the congregation, the motivation to establish new congregations, diverse outreach strategies, and geo-political conditions that were conducive to reaching nations outside of the world. Jews with the Gospel of Jesus Christ. Therefore, the yellowing harvest fields in Asia Minor became the target of their ministry to establish a church. The uniqueness of the Early Church can inspire church members in Indonesia to take advantage of conducive geo-political factors in order to reach open ethnic groups and are ready to be harvested.ABSTRAK: Problem artikel ini membahas faktor yang menantang dan yang menentukan bagi perluasan misi Gereja Mula-mula di Asia Kecil, mulai dari Yerusalem sampai ke Roma. Faktor-faktor penentu itu memungkinkan perluasan misi Gereja dapat ini dapat dijadikan patokan bagi gereja sepanjang abad dalam bermisi. Kajian artikel ini menggunakan metode deskriptif. Hasilnya, menunjukkan orang Kristen mula-mula melaksanakan Amanat Agung demi perluasan misi gereja karena didukung oleh ketaatan para pemimpin dan warga jemaatnya, motivasi untuk mendirikan jemaat baru, strategi penjangkauan yang beragam, dan kondisi geo-politik yang kondusif untuk mencapai bangsa-bangsa di luar Yahudi dengan Injil Yesus Kristus. Oleh karena itu, ladang tuaian yang menguning di Asia Kecil menjadi terget pelayanan mereka untuk mendirikan jemaat. Keunikan Gereja Mula-mula ini dapat menginspirasi warga gereja di Indonesia agar memanfaatkan faktor geo-politik kondusif guna mencapai suku-suku bangsa yang terbuka dan siap dituai.Kata kunci: Gereja mula-mula, Perluasan Injil, faktor penentu, teladan pemimpin